Instruments économiques et réglementaires au profit du développement des micro, petites et moyennes entreprises (MPME) en Haïti - Philippe Simon (Études Caribéennes)
This study assesses the place of MSMEs in Haiti and gives a brief description of the relevant economic, regulatory and technological instruments of economic development and environmental protection. The discussions suggest that the application of such instruments will encourage and improve economic development in Haiti.The infrastructure necessary for MSEs drives growth and offers added value to economic development in Haiti. With an overview of Haitian MSEs we have been able to identify and palliate insufficiencies in the legislative framework regulating the operation of MSEs, as well as, understand their involvement in economic growth. MSEs are a powerful tool to reduce poverty, facilitate economic development and reinforce policies supporting environmental protection.